Structuring Model for Corporate Productive Cash-Waqf in Indonesia - Bambang Tutuko; Ahmad Hudaifah; Andi Zulfikar (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2017)
The development of waqf in Indonesia has attracted plenty discussion in third sector economy model (voluntarily sector) to overcome social economic problems. Semen Indonesia is giant multinational state-owned company with various program of community service potentially adopting cash waqf as an innovative support for financing socio economic program for benefiting surrounding society. The study has utilized qualitative data by analyzing important and relevant secondary data, direct observation in Semen Indonesia Group, and conducting interview with key informants. The productive cash waqf model is newly developed corporate waqf equipped with information technology system E-waqf application to encourage Semen Indonesia’s big community to donate in cash waqf program. The fund accumulation is managed in profitable investment around Semen Indonesia and society environment. The financial and managerial system of Semen Indonesia Company and holding is possibly adopting the productive cash waqf concept when managed properly and transparently